1999
DOI: 10.1037/h0080427
|View full text |Cite
|
Sign up to set email alerts
|

Subjective experience in schizophrenia: Factors influencing self-esteem, satisfaction with life, and subjective distress.

Abstract: The relative and combined effects of individual characteristics, severity of illness, psychosocial functioning, treatment intensity, and milieu variables on self-esteem, distress and satisfaction with life were examined in a study of 103 subjects diagnosed with schizophrenia or schizoaffective disorder, all of whom had been in either high-intensity or low-intensity community-based interventions for at least six months. Implications of the findings for treatment and for research on subjective experience in schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 31 publications
5
29
1
2
Order By: Relevance
“…Results are largely consistent with the results of previous studies of the correlates of hope [22][23][24][25][26][29][30][31]. Both the expectation of success in the future and the expectation of being able to persist were linked to lesser levels of stigma, fewer symptoms, lesser anxiety, and lesser preference for avoidant forms of coping.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Results are largely consistent with the results of previous studies of the correlates of hope [22][23][24][25][26][29][30][31]. Both the expectation of success in the future and the expectation of being able to persist were linked to lesser levels of stigma, fewer symptoms, lesser anxiety, and lesser preference for avoidant forms of coping.…”
Section: Discussionsupporting
confidence: 82%
“…As persons encounter and accept stigma, the possibility of future fulfillment may seem increasingly remote. At the clinical level, hope has been suggested to be influenced by positive and negative symptoms and depression [24][25][26][27][28]. Experiencing symptoms has been suggested to be naturally demoralizing and leads to fewer positive expectations for the future.…”
Section: Introductionmentioning
confidence: 99%
“…A small body of research has examined the correlates of self-esteem among persons with schizophrenia (e.g., Bradshaw & Brekke, 1999;Markowitz, 2001;Roe, 2003;Torrey, Mueser, & Drake, 2000); these studies have consistently demonstrated that self-esteem is significantly correlated to life satisfaction. A longitudinal study demonstrated, however, that baseline selfesteem does not predict life satisfaction (Roe, 2003), but rather that changes in self-esteem are associated with changes in life satisfaction.…”
Section: Enduring Environmental Conditions and Copingmentioning
confidence: 99%
“…The causal relationship is, though, not clear in these studies. Further, higher self-esteem at the end of treatment has been found to be related to a lower degree of anger in the treatment milieu (Bradshaw & Brekke, 1999). Facilitating possibilities for the patients to engage in positive interpersonal relationships-both with the treatment staff and with family and friends during treatment-may therefore be an important element…”
Section: The Clinical Importance Of the Findingsmentioning
confidence: 98%